(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2017)
‘Human Resource’ is one of the very important assets for any organization and in this competitive and global environment it has actually become imperative for any organization to retain competent employee for survival of the business. Organization success depends not only on how it makes the most of human competences, but also how it stimulates commitment to an organization. Competency based management approach concentrates on increasing the potential of employee and to have the competitive edge over other organizations in today’s time. Employee’s commitment, in concert with a competent workforce is significant for the organization to be able to compete in quality and to go along with global changes. The framework is now being applied in the different practices of human resource management i.e. recruitment and selection, training and development, career development, compensation and benefits etc. Various Researchers and scholars have reported that competency based management has a positive outcome on the performance of organization as well as of the employees. The concept is now being used as a tool for the success of the organization. This paper is an attempt to through light on the concept as well as it reviews the available literature of competency based management and its importance from the perspective of the organization as well as of the employees.